Sexual citizenship through resistance: a movement that centers disabled women’s voices - MacKeigan, Tanya (Disability & Society, 2021)
This research examines the discourses that shape disabled women’s sexual subjectivity. I wanted to see how disabled women’s understanding of themselves as sexual is socially influenced. I held a focus group and individually interviewed five self-identified physically disabled women about their sexual lives. They shared detailed stories of personal experiences and societal influences. The main social influences that were present in the women’s stories were ableism, sexism, and resistance; the focus of this article is resistance. Resistance discourses challenge mainstream notions of disability and sexuality and combat the oppression that ableism and sexism can create. It is important work to highlight these resistance narratives; they are often overlooked in society. Diverse social understandings of disability and sexuality are needed, and it is important that they come from disabled people. This research seeks to make space for disabled perspectives in the interest of sexual inclusivity and sexual citizenship for disabled women.
Keywords: 2000 à aujourd'hui; 2010-2019; 2020-2029; EDI; accessibilité; amériques; approches et analyses; canada; capacitisme; care; colombie-britannique; corps; cours; discipline; droit des personnes en situation de handicap; intersectionnalité; premier cycle; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sex1911; sex1920; sexisme; sexualité; systèmes d'oppressions; thématiques; travail social; études critiques du handicap

Femmes et handicap - Masson, Dominique (Recherches féministes, 2013)
Les femmes handicapées, leurs réalités et leurs combats sont encore largement absents du courant de pensée majoritaire (mainstream) en études féministes qui, malgré un virage récent vers les analyses intersectionnelles, demeurent peu au fait des modalités d'analyse du handicap et des oppressions fondées sur les (in)capacités. Cet article veut permettre à un lectorat francophone de se familiariser avec les principales bases conceptuelles utilisées pour théoriser le handicap et les (in)capacités développées dans le domaine des études critiques du handicap, et en particulier par les auteures féministes travaillant dans ce champ. Il vise également à contribuer aux connaissances féministes des enjeux de transformation sociopolitique qui sont centraux pour les femmes handicapées, tels que ceux-ci sont révélés par les luttes de l'organisation féministe Action des femmes handicapées (Montréal). En conclusion, l'auteure explique la raison pour laquelle le handicap doit être considéré comme un enjeu féministe
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; EDI; amériques; approches et analyses; canada; capacitisme; care; corps; cours; discipline; histoire et politique; intersectionnalité; justice sociale; premier cycle; périodes historiques; québec; ressource en ligne; régions géographiques; santé; sciences humaines; sciences sociales; sex1920; sexisme; systèmes d'oppressions; thématiques; études critiques du handicap; études féministes

Ecrire comme vivre: dans l'hybridite: entretien avec Anne-Marie Alonzo - Dupre, Louise (Voix et Images, 1994)
Keywords: EDI; amériques; approches et analyses; arts; canada; capacitisme; cours; discipline; lit2815; lit3495; premier cycle; québec; régions géographiques; systèmes d'oppressions; thématiques; écriture des femmes*; études littéraires

Contexte de vulnérabilité : femmes handicapées | INSPQ - Levasseur, Karine (Institut national de santé publique du Québec)
Keywords: EDI; amériques; approches et analyses; canada; capacitisme; care; cours; discipline; intersectionnalité; inégalités; justice sociale; premier cycle; québec; ressource en ligne; régions géographiques; santé; sex1920; sexisme; systèmes d'oppressions; thématiques